Fail-safe transcriptional termination for protein-coding genes in S. cerevisiae. - Rondón, A; Mischo, H; Kawauchi, J; Proudfoot, N (2009)
Transcription termination of RNA polymerase II (Pol II) on protein-coding genes in S. cerevisiae relies on pA site recognition by 3' end processing factors. Here we demonstrate the existence of two alternative termination mechanisms that rescue polymerases failing to disengage from the template at pA sites. One of these fail-safe mechanisms is mediated by the NRD complex, similar to termination of short noncoding genes. The other termination mechanism is mediated by Rnt1 cleavage of the nascent transcript. Both fail-safe termination mechanisms trigger degradation of readthrough transcripts by the exosome. However, Rnt1-mediated termination can also enhance the usage of weak pA signals and thereby generate functional mRNA. We propose that these alternative Pol II termination pathways serve the dual function of avoiding transcription interference and promoting rapid removal of aberrant transcripts.